Short-time changes in coronary artery plaques assessed by follow-up coronary CT angiography: characteristics and impact on patient management - Görich, Hanna Maria; Buß, Sebastian Johannes; Emami, Mostafa; Seitz, Sebastian; Loßnitzer, Dirk; Fortner, Philipp; Baumann, Stefan; Brado, Matthias; Gückel, Friedemann; Sokiranski, Roman; Sommer, André; Görich, Johannes; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Coronary artery disease (CAD) shows a chronic but heterogeneous clinical course. Coronary CT angiography (CTA) allows for the visualization of the entire coronary tree and the detection of early stages of CAD. The aim of this study was to assess short-time changes in non-calcified and mixed plaques and their clinical impact using coronary CTA in a real-world setting.Methods: Between 11/2014 and 07/2019, 6,701 patients had a coronary CTA with a third-generation dual-source CT, of whom 77 patients (57 males, 63.8 ± 10.8 years) with a chronic CAD received clinically indicated follow-up CTA. Non-calcified and mixed plaques were analyzed in 1,211 coronary segments. Patients were divided into groups: stable, progressive, or regressive plaques.Results: Within the follow-up period of 22.3 ± 10.4 months, 44 patients (58%) showed stable plaques, 27 (36%) showed progression, 5 (7%) showed regression. One patient was excluded due to an undetermined CAD course showing both, progressive and regressive plaques. Age did not differ significantly between groups. Patients with plaque regression were predominantly female (80 vs. 20%), whereas patients showing progression were mainly male (85 vs. 15%; p < 0.01 for both). Regression was only observed in patients with mild CAD or one-vessel disease. The follow-up CTA led to changes in patient management in the majority of subjects (n = 50; 66%).Conclusions: Changes in coronary artery plaques can be observed within a short period resulting in an adjustment of the clinical management in the majority of CAD patients. Follow-up coronary CTA renders the non-invasive assessment of plaque development possible and allows for an individualized diagnostics and therapy optimization.
Gesehen am 25.08.2021